Thrombolysis with saruplase versus streptokinase in acute myocardial infarction: five-year results of the PRIMI trial - Spiecker, Martin; Windeler, Jürgen; Vermeer, F.; Michels, R.; Seabra-Gomes, R.; vom Dahl, J.; Kerber, S.; Verheugt, F. W.; Westerhof, P. W.; Bär, F. W.; Nixdorff, U.; Barth, H.; et al. (American heart journal, 1999)
BACKGROUND: Short-term safety and efficacy of thrombolysis with saruplase in acute myocardial infarction have been shown in several trials. To assess long-term outcome of patients treated with saruplase or streptokinase for myocardial infarction, a 5-year follow-up of patients included in the Pro-Urokinase in Myocardial Infarction Trial was performed. METHODS AND RESULTS: Follow-up data are available from 8 centers on 255 (92.4%) of 276 included patients. The 5-year mortality rate was comparable with 20.8% of patients in the saruplase group and 16.9% in the streptokinase group (odds ratio 1.29, 95% confidence interval 0.69 to 2.42). In both groups, a considerable number of fatal cardiovascular events occurred more than 1 year after study inclusion. Rates of percutaneous transluminal coronary angioplasty and coronary artery bypass grafting were comparable in both groups. Reinfarction within 5 years occurred in 19.0% of patients in the saruplase group and tended to be less frequent at 10.8% after streptokinase treatment (odds ratio 1.94, 95% confidence interval 0.98 to 3.84). In both groups, the majority of reinfarctions took place more than 3 months after study inclusion. The 5-year stroke rate was 3.6% and 7.2% in the saruplase and streptokinase groups, respectively (odds ratio 0.49, 95% confidence interval 0.16 to 1.47). Subjective symptoms of heart failure and angina pectoris were comparable in both groups. CONCLUSIONS: Our data are consistent with a similar long-term outcome for patients treated with saruplase or streptokinase. Despite the low-risk profile of the patient cohort, there were considerable adverse event rates over a 5-year period.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 26.04.2021